Discrete-time deadbeat control for STATCOMs based on dq reference frame: a high-speed, tuning-free strategy for reactive current regulation - Liang, Haiyang; Minfu, A.; Zhang, Yanbin; Zhang, Yi; Zhan, Shiguang; Zhang, Yunlong; Zhang, Yiwen; Tian, Zhenhua (Frontiers in Energy Research, 2025)
The increasing penetration of distributed generation and the evolving requirements of smart grids have heightened the demand for fast, accurate, and robust reactive power control in Static Synchronous Compensators (STATCOMs). While proportional-integral (PI) controllers remain widely adopted, their reliance on iterative tuning and limited performance under low switching frequencies restricts their application in modern high-voltage cascaded H-bridge (CHB) systems. This paper proposes a novel discrete-time deadbeat current control method formulated directly in the synchronous rotating dq reference frame. By transforming AC currents into DC signals, the control structure is simplified and enables precise decoupled regulation of active and reactive currents. Unlike conventional approaches that discretize analog-domain designs, the proposed controller is derived analytically in the discrete domain, eliminating the need for parameter tuning or empirical adjustment. Simulation studies confirm that the approach achieves excellent current tracking accuracy, robust performance under ±10% inductance and −10% to +40% resistance variations, and maintains low total harmonic distortion even at low switching frequencies. These features make the method particularly suitable for high-voltage cascaded H-bridge STATCOM applications. Furthermore, stability analysis demonstrates that the closed-loop poles remain inside the unit circle across parameter deviations, ensuring reliable operation. The results indicate that the proposed approach provides a practical, fully digital control solution that improves accuracy, robustness, and implementation efficiency in modern smart grid environments.